Analysis of Salt Hydrolysis Misconception With False Statements After Application of Guided Inquiry Assisted by E-Laboratory Instruction (Universitas Negeri Semarang, 2020)
Salt hydrolysis is a difficult chemical concept because it is microscopic and abstract. These properties can occur misconceptions. The misconception in this material is quite high and is spread across all concepts. Submission of this material with appropriate learning methods and models is expected to reduce student misconceptions. Therefore, it is necessary to conduct research aimed at studying the results of the analysis of salt hydrolysis misconceptions after the application of guided inquiry assisted by e-laboratory instructions. This research was conducted at Jekulo 1 High School in the 2018/2019 academic year with 104 research subjects. The method used in this research is quantitative description method. The results obtained showed that students' misconceptions of salt hydrolysis material after the application of guided inquiry assisted by e-laboratory instructions were still high. The results of misconception analysis on salt hydrolysis materials were 47.50%. Misconceptions regarding changes in color in a salt solution, ionic equilibrium in a salt solution, experimental experiments to predict the pH of a salt solution, the acidic acidic nature of a salt solution, and the pH of a suitable salt solution were 41.35%; 62.50%; 35.58%; 37.02%; and 61.06%.